PENYULUHAN GIZI MENGGUNAKAN MEDIA BOOKLET TERHADAP PENGETAHUAN IBU TENTANG POLA MAKAN ANAK PRASEKOLAH - S.KM, M.PH, YULI LARAENI (LPSDI Bina Patria, 2024)
Background. Good food consumption patterns will have a positive effect on a person's health such as preventing or helping to cure disease. Vice versa, if the pattern of food consumption is not good it will affect the nutritional status of children. Diet can be measured quantitatively by looking at the type of food, weight, portion and frequency, while qualitatively it can be seen through the type and composition of food only.The results of RISKESDAS 2018 nationally according to the BMI/U index for the problem of obesity prevalence of 10.8% and thin of 6.8%. NTB Province has a fat prevalence of 5.35% and a lean prevalence of 13.24%. In West Lombok, the prevalence of obesity is 5.31% and the prevalence of thinness is 14.19%. Research Methods. This research is a quasi-experimental using a treatment group (experimental) and a control group. The treatment group was given nutritional counseling about the diet of preschool children using booklet media, while the control group was only given nutritional counseling about the diet of preschool children without using booklet media. The design used is Pretest Posttest With Control Group. Analyzed by statistical analysis using the Independent Samples T Test. Results. There was a difference in the average value in the treatment group and the control group on the level of mother's knowledge about the eating patterns of preschool children in Arroziqin PAUD with a probability value = 0.000 ( p<0.05).